Politics, Society and Culture in Orthodox Theology in a Global Age - Großhans, Hans-Peter; Kalaïtzidēs, Pantelēs (Eastern Church Identities, 2022)
The articles in the book show that today’s Orthodox theology is constructively relating to modernity in politics, society and culture. In 20 articles very prominent Orthodox theologians and experts on Orthodox theology and Orthodox Christianity from academic fields like sociology of religion or political studies are discussing, in what sense politics, society and culture are considered in Orthodox Theology in a global horizon. Contributors are Alfons Brüning, Ina Merdjanova, Nathaniel Wood, Cyril Hovorun, Dimitrios Moschos, Lucien Turcescu, K. M. George (Kondortha), Pantelis Kalaitzidis, Branko Sekulić, Georgios Vlantis, Nikolaos Asproulis, Atanas Slavov, Sveto Riboloff, Haralambos Ventis, Ioannis Kaminis, Irena Pavlović, Athanasios N. Papathanasiou, Chris Durante, Kateřina Kočandrle Bauer, Vasilios N. Makrides